Understanding socio-demographic patterns and wellbeing dimensions of the elderly in Malaysia: the way forward in reaching an age nation by 2030 / Aslinda Ramely, Yarina Ahmad and Nor Hafizah Mohamed Harith - Ramely, Aslinda; Ahmad, Yarina; Mohamed Harith, Nor Hafizah (Faculty of Administrative Science & Policy Studies (FASPS), Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
While most of the dominant countries in the world such as Africa, Asia, Europe, Oceana, Latin America, the Caribbean, and North America are experiencing the increasing number of the elderly, the issue of the ageing population becomes a global phenomenon. In the meantime, Malaysia is also among the countries which is located in the Asian region which is a contributor to the overall world ageing population. Previously in the 1950s and 1990s, the population of the elderly in Malaysia has been recorded to be lower and has fluctuated in trend. However, since the year 2000 until recent years, the elderly population in this country has been observed to drastically increase, reaching 2.653 million in the year 2014, as compared to only 386.6 thousand in 1960. As forecasted by the United Nations, this increment will transform Malaysia into an aged nation by 2030. While the elderly population is growing yearly, extra attention needs to be given to the elderly in ensuring their wellbeing at an optimum level. Only then, may this country evolve and prosper into a better place for all, especially the elderly. Hence, the understanding of socio-demographic patterns of the elderly is highly needed to obtain a profound understanding of their demands. For this reason, the primary objective of this concept paper is to analyses four patterns of the socio-demographic of Malaysian elderly namely in terms of their age group, gender, geographical area and level of education. Furthermore, this paper scrutinises the applicability of these socio-demographic patterns in attaining five wellbeing dimensions of the elderly which are the economy, environment, health, social and on spiritual terms. Hence, this paper concludes that a thorough understanding of socio-demographic patterns and wellbeing dimensions of the elderly are important for the government and all relevant parties to develop necessary actions precisely for this age group alongside also strategising on ways to propel forward to be a prosperous aged nation by 2030.